An Overview on the Possibility of Scandium and REE Occurrence in Sulawesi, Indonesia - Maulana, Adi; Sanematsu, Kenzo; Sakakibara, Masayuki (Geological Agency, 2016)
DOI:10.17014/ijog.3.2.139-147The development in modern-high technology application is growing rapidly, resulting in the constant supply of critical metal and rare earth elements (REE). Currently, resources of these elements are restricted and new source of these elements need to be discovered accordingly. Scandium (Sc) as one of critical metals is an important metal for electrolyte of solid oxide fuel cells and other advance technology. In addition, REE are the important elements in the use of permanent magnets and rechargeable batteries. This manuscript reports an overview on the possibility of scandium and rare earth element occurrences in Sulawesi. Sc is concentrated in limonite layers in Soroako ultramafic rocks as a result of Fe3+ site substitution of mafic minerals (pyroxene, amphibole, etc.) during a laterization process. REE are enriched in association with clay minerals in B horizon from heavily weathered granitic rocks in Palu and Masamba, suggesting the possibility of ion-adsorption style mineralization. The lateritic soil of the ultramafic rocks and the weathered crusts of the granitic rocks in Sulawesi could be the potential sources of scandium and rare earth elements, respectively.